Multifactorial intervention in diabetes patients - Czupryniak, Leszek (Przewodnik Lekarza/Guide for GPs, 2006)
Two million people are estimated to have diabetes in Poland, and in addition diabetes incidence has been clearly rising in Poland in recent years. The main health problem in diabetes is its complications in cardiovascular and nervous systems, which eventually lead to increased incidence of coronary heart disease, stroke, limb amputations, and vision impairment. United Kingdom Prospective Diabetes Study have shown that antihyperglycemic treatment does not effectively prevent the development of cardiovascular complications of diabetes. To achieve this, blood pressure and blood lipids must be assessed and treated if found abnormal. Moreover, each patient with diabetes should be treated with acetylsalicylic acid if not contraindicated and should be offered an effective smoking cessation help. Steno-2 study has shown that such multifactorial intervention may reduce micro- and macroangiopathy by over 50% in less than 8 years.